Structural Study of Highly Deformed Meguma Phyllite and Granite Vicinity of White Head Village, S.E. Nova Scotia - Mawer, C. K.; Williams, P. F. (Atlantic Geoscience, 1986)
A long history of dextral transcurrent shear on the Cobequid-Chedabucto Fault System is indicated by structures in Meguma Zone phyllite and granite, and late veins, which outcrop close to the present Chedabucto Fault trace. The phyllite deformed first upon collision of Meguma with Avalonia during the Acadian Orogeny, and progressively since that time by ductile deformation mechanisms for almost the total deformational history of the rocks. Its foliation is due to transposition and dynamic recrystallization. Granite vas intruded syntectonically, as shown by contact oetamorphic formation of syntectonic porphyroblasts in the phylllte which are rotated, and progressive development of an inhomogeneous shear zone foliation towards the phyllite-granite contact. This foliation is approximately parallel to that developed in the phyllite. Quartz veins, which overprint all earlier structures, were deformed and accomodated by ductile mechanisms while being rotated in the continued progressive dextral shear regime. RÉSUMÉ Une longue histoire de cisaillent transversale dextrale, sur les systèmes de failles Cobequid-chedabucto, est indlque par des structures dans les phylites et les granites Meguma et les jeunes veines qui affleurent près de la trace de la faille Chedabucto actuelle. La phylite c’est d’abord déformé à la suite de la collision entre Meguma et Avalonia pendant l’orogénèse Acadienne, et dépuis par des mécanismes progressifs de déformation ductile pendant presque toute la durée de l’histoire déformationelle des roches. Sa foliation est attribute à la transposition et à la recristalisation dynamique. Le granite a été pénétré syntectoniquement, comme le demontre la formation de porphyroblastes syntectoniques par moyen de métamorphisme de contact, dans les phylites retournées, et par le développement progressif d’une foliation de zone de cisaillement inhomogène vers le contact phylite-granite. Cette foliation est plus ou mollis paralèlle à celle qui est développée dans la phylite. Des veines de quartz, qui surimpose toutes les structures précedences, ont été déformées et accomodées par des mécanismes ductile, pendant qu’elles étaitant retournées par le régime progressif de cisaillement déxtral [Traduit par le journal]